The Effectiveness of Social Media Advertising and Brand Image in Attracting New Students in College : (Case Study on the Global Institute) - Teodora Septiana; Winanti Winanti; Karnawi Kamar; Tiana Indry Gunawan; Indah Anggraeni Purnama Sari (Pusat Riset dan Inovasi Nasional, 2025)
Social media has become a strategic instrument in the promotion of higher education institutions to attract the interest of prospective students in the contemporary digital era. This study explores the effectiveness of the implementation of social media advertising on the increase in the number of new students, by considering the role of brand image as an intervening variable, using the theoretical framework of the Hierarchy of Effects Model which describes the stages of the marketing communication process. Through a quantitative methodology with a survey technique on 150 respondents of grade XII high school students in the Tangerang area who were active on social media platforms, multiple linear regression analysis revealed the positive and significant influence of social media advertising, both directly and through strengthening brand awareness and brand image, with t-values of social media advertising (5,527 > t table 1,989) and brand awareness (7,967 > t table 1.989). The simultaneous analysis confirmed the collective influence with F count 54,956 > F table 3,195 at a significance of 0.000, where the research model explained 68% of the variability in the increase in the number of students (R-square = 0.688), while 31.2% was influenced by external factors, emphasizing the importance of a social media advertising strategy that is integrated with the development of a positive brand image in increasing the attractiveness of higher education institutions